The Development of an Intelligent Leadership Model for State Universities - Aleme Keikha; Reza Hoveida; Nour Mohammad Yaghoubi (Foresight and STI Governance, 2017)
Higher education and intelligent leadership are considered important parts of every country’s education system, which could potentially play a key role in reaching the goals of society. In theories of leadership, new patterns attempt to view leadership through the prism of creative and intelligent phenomenon. This paper aims to design and develop an intelligent leadership model for public universities. A qualitative-quantitative research method was used to design a basic model of intelligent leadership. The opinions of pundits and experts with a purposive sampling method to achieve theoretical saturation was used to design a model in the qualitative phase. During model testing based on confirmatory factor analysis, data indicated that dimensions of intelligent leadership were placed in the four components: rational leadership, emotional leadership, spiritual leadership and collective leadership and classified in sub-categories. Rational leadership was classified into five sub-categories (strategic thinking, common targeting, planning, decision-making and monitoring and feedback); emotional leadership was classified into four sub-categories (self-awareness, self-management, motivation and social awareness); spiritual leadership was classified into seven sub-categories (vision, belief in achieving this goal, altruism, meaningful work, membership, organizational commitment and feedback); and finally, collective leadership was classified into the three sub-categories (communication, development of a communication network and –an exchange of opinions between the leader and team). The results presented in the paper correspond with statistical logic. Finally, the test model and the Delphi technique were applied using the survey approach and the ultimate model was described, including 426 codes, 89 sub-categories and four main categories (rational leadership, emotional leadership, spiritual leadership and collective leadership).